Understanding diversity and distribution of the insect assemblages associated with carrions - Do, Yuno; Lee, Seung Yeon; Chung, Ki Wha; Moon, Tae-Young (Journal of forensic and legal medicine, 2019)
375 case studies from 120 publications published over the last three decades on forensic entomology were reviewed to determine how many carcass-associated insects have been described globally and which species are relatively important among carcass-associated insects. A total of 1213 carcass-associated insects belonging to 91 families of 10 orders were described from 375 case studies in nine habitat types of 30 countries with 24 subjects including humans and non-human animals. There were 564 and 515 species from the orders Diptera and Coleoptera, respectively, which was almost 90% of the total species recorded. The richness and distribution of dead body-associated insects considerably differed among countries, habitats, and dead body types. We propose some species based on criteria including distribution, occurrence frequency, and resource preference. •1213 carcass-associated insects were described from 375 case studies in 30 countries with 24 dead body types.•The richness and occurrence of carcass-associated insects considerably differed among countries, habitats, and carcass types.•There may be differences between the insect assemblages associated with human and non-human bodies.